Analysis of the Meaning of Rada’ah in QS. al-Baqarah [2]: 233 and Its Implications for Divorce Law - Rismayanti, Izzuma Tasya; Sofie Mayda Sugihfauzia Permana; Mohammad Athoillah; Ali Khosim (Jurnal Semiotika Quran, 2025)
This study discusses the meaning of rada’ah in QS. al-Baqarah [2]: 233 and its implications for divorce law. This verse affirms the mother's right to breastfeed her child for two full years for those who wish to complete the breastfeeding period, while emphasizing the father's obligation to provide for the mother and child in a ma'ruf manner. Using qualitative-descriptive methods with library research, this article applies ijmali and tahlili interpretations to understand the global and detailed meaning of the verse, and examines its impact on the rights, obligations, and protection of children after divorce. The results of the study indicate that the meaning of rada’ah encompasses biological, legal, social, and emotional dimensions. Through ijmali interpretation, this verse is understood globally as the principle of balance between parental rights and obligations, while tahlili interpretation emphasizes legal details related to maintenance, breastfeeding, weaning, mahram rights, and child protection. Implications for divorce law include the father's obligation to provide for a nursing mother, the mother's primary right to care for the child during the breastfeeding period, and the principle of deliberation in weaning children before two years of age. This research confirms that the concept of rada’ah serves as a normative foundation for maintaining justice, the welfare of children, and the continuity of parental relationships even after divorce, in line with Islamic law and Indonesian national law. The contribution of this research lies in the integration of ijmali and tahlili interpretations with contemporary family law studies, thus positioning rada’ah as the basis for child protection and post-divorce arrangements for support and care.